EP‐efficient 1,2,4‐dithiazolines and their tribological effect on steel bearing balls of different composition - Bhattacharya A.; Verma V.K. (My University, 2025)
This paper deals primarily with the potential extreme‐pressure (EP) activity of certain cyclic disulphide additives in paraffin oil. The antiwear and antifriction properties of 1,2,4‐dithiazo‐line additives have been evaluated on a four‐ball machine by using 12.7 mm diameter steel ball bearing specimen‐I. The paper also includes a discussion on the effectiveness of 3‐p‐Cl‐phe‐nylimino‐5‐(N‐methylphenyl)amino‐1,2,4‐dithiazoline on steel bearing balls of different compositions. The topography and the surface chemistry of the bearing ball wear scar were studied by Scanning Electron Microscopy (SEM) and Auger Electron Spec‐troscopy (AES). Copyright © 1992 John Wiley & Sons, Ltd